Nuclear energy in Southeast Asia : competition or cooperation? - Chew, Alvin (2011)
Southeast Asia is expected to see the operation of its first nuclear power plant by 2020. While this will alleviate concerns over energy security and carbon emissions, will the advent of nuclear reactors spark a nuclear energy race in the region?